2014
DOI: 10.1002/gps.4074
|View full text |Cite
|
Sign up to set email alerts
|

The effects of combine treatment of memantine and donepezil on Alzheimer's Disease patients and its relationship with cerebral blood flow in the prefrontal area

Abstract: In this study, by administering memantine in AD patients that inhibit the reduction of cerebral blood flow in the prefrontal area and improve clinical symptoms overall cognitive function, behavioral and psychological symptoms of dementia, thereby reducing the care burden of caregivers was suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 17 publications
0
37
0
Order By: Relevance
“…The results of previous studies are possible to be overestimated if their literature search was incomplete. When we compared the date of literature search in the previous meta-analyses with the date of existing literature in our study, we found that 2 open-labeled trials 23,27 were excluded in the study by Farrimond et al 8 ; 5 articles 23,25e28 were missed in the study by Muayqil and Camicioli 7 ; and 7 articles 20,22,23,25,27,28,31 were missed in the study by Matsunaga and colleagues. 9 This study focused on only 1 instrument for each domain of cognitive function, activities of daily living, neuropsychiatric symptoms, and global changes.…”
Section: Discussionmentioning
confidence: 83%
“…The results of previous studies are possible to be overestimated if their literature search was incomplete. When we compared the date of literature search in the previous meta-analyses with the date of existing literature in our study, we found that 2 open-labeled trials 23,27 were excluded in the study by Farrimond et al 8 ; 5 articles 23,25e28 were missed in the study by Muayqil and Camicioli 7 ; and 7 articles 20,22,23,25,27,28,31 were missed in the study by Matsunaga and colleagues. 9 This study focused on only 1 instrument for each domain of cognitive function, activities of daily living, neuropsychiatric symptoms, and global changes.…”
Section: Discussionmentioning
confidence: 83%
“…We did not retrieve 10 studies by searching through the review articles and clinical trial registries (Figure S1). Although 30 studies were identified though the literature search, only 11 studies (memantine monotherapy vs placebo: four studies,14,17,20,21 n=1,500; combination therapy with memantine and cholinesterase inhibitors vs cholinesterase inhibitors: seven studies,15,18,2226 n=2,761) were included in the meta-analysis, since the other 20 studies did not report any available data for performing a meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The mean duration of the studies was 26.5 weeks (one study was 52 weeks, other studies were 24 weeks), the mean patient age was 76.3 years, and the percentage of males was 34.6%. Although one of the 11 studies was an open-label study (ie, not placebo-controlled study),22 the other 10 studies were double-blinded, randomized, placebo-controlled trials. One study was a memantine extended-release study 23.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we have reported that memantine administered to patients with moderate to severe AD may inhibit the reduction of cerebral blood flow in the prefrontal area, improve global clinical symptoms, cognitive function and BPSD, and lighten the burden of care placed on caretakers [23]. Although each medication has the effect of improving cognitive function for a certain period and delaying cognitive dysfunction, they still cannot treat the clinical condition for a long time.…”
Section: Research Rei Wakementioning
confidence: 99%